APPLICATION OF DATA ENVELOPMENT ANALYSIS AND MALMQUIST INDEX ON THE MEASUREMENT OF EFFICIENCY AND PRODUCTIVITY: A CASE STUDY OF RUBBER PRODUCTION IN SOUTHERN THAILAND - Parichatnon, Surakiat; Maichum, Kamonthip; Peng, Ke (PEOPLE: International Journal of Social Sciences, 2017)
The purpose of this study is to investigate the relative technical efficiency of rubber production in Southern of Thailand using the Data Envelopment Analysis (DEA) during the period 2007–2016. Moreover, Malmquist productivity index (MPI) was used to investigate the changes of rubber production efficiency and estimates of the rubber productivity trend. The findings indicated that Trang city has most effective and suitable for the production of rubber when compared to other cities in Southern Thailand. On the other hand, the results also showed that Phuket city has worst scores of efficiency and declination of rubber production. Moreover, MPI model showed the upward productivity trend of rubber production during the time period of the study. The findings from this study can provide important information to farmers, rubber research institutes and Thai government for determining effective strategies to improve productivity and technical efficiency of rubber production. Thai government and rubber research institutes should provide the knowledge, management skills and correct production skills for rubber farmers. Furthermore, rubber research institutes should be at the forefront to increase the rubber yields and provide funding to farmers for increase sustainable rubber production.